Fluorodeoxyglucose Positron Emission Tomography Can Provide Useful Information for Differentiating Thymic Epithelial Tumors - Tomita, Masaki; Ayabe, Takanori; Tsuchiya, Kazuyo; Nakamura, Kunihide (The Thoracic and Cardiovascular Surgeon, 2018)
Background We examined the usefulness of fluorodeoxyglucose (FDG) positron emission tomography (PET) in predicting the World Health Organization (WHO) histologic type and Masaoka stage of thymic epithelial tumors.Methods A total of 73 patients with thymic epithelial tumors who underwent preoperative FDG-PET were included. Relationships between the maximum standardized uptake value (SUVmax) and WHO histologic type and the Masaoka stage of the tumor were examined. Differences in SUVmax between the various groups were calculated. To avoid the effect of the tumor size on SUVmax, the ratio of SUVmax to tumor size (SUVmax/T) was also examined.Results There was a significant relationship between SUVmax and WHO histologic type. SUVmax of high-risk thymomas (types B2 and B3) was significantly higher than that of low-risk thymomas (types A, AB, and B1). SUVmax of thymic carcinomas was also significantly higher than those of the low-risk and high-risk groups. The relationship between the SUVmax/T and WHO histologic type showed more significant results. SUVmax and SUVmax/T showed higher values in patients with advanced Masaoka stage disease than in those with early-stage disease.Conclusions FDG-PET can provide useful information for differentiating thymic epithelial tumors. The SUVmax/T is more useful than the SUVmax for differentiating between low-risk and high-risk thymomas.
Keywords: thymic epithelial tumor; WHO classification; FDG-PET; Masaoka stage